Inflation, price stops and price controls - Karlheinz Kleps (Intereconomics, 1973)
It has been quite obvious for several years already that the attempts to achieve the aim of price stability are running into the greatest difficulties. While the rates of inflation are escalating in almost all countries, it is becoming increasingly clear at the same time that the authorities endeavouring to stabilise the level of prices are faced by problems of great complexity.
Keywords: 330; Economic Policy